Residual activity of herbicides used in soybean agriculture on grain sorghum crop succession - Dan,H.A. (2010)
The sorghum is a kind of prominence before the cultures used in succession in the Brazil. However, little information concerning the effects of residual activity of herbicides on the crop in this region are known. The objective of this study was to evaluate the residual activity of herbicides used in weed management in soybeans as well as check their effects on grain sorghum grown in succession. For the field experiment, we used a randomized block design with four replications. Eight herbicide treatments were evaluated: imazaquin (0,161 kg ha-1), diclosulam (0,035 kg ha-1), sulfentrazone (0,600 kg ha-1) and flumioxazin (0,05 kg ha-1) in applications made before emergency and chlorimuron-ethyl (0,015 kg ha-1), imazethapyr (0,060 kg ha-1), imazethapyr (0,100 kg ha-1) and fomesafen (0,250 kg ha-1) applied post-emergence soybean (V3 stadium, 18 DAE), and a control without herbicide application. The grain sorghum (cv. AG-1040) was sown after the harvest of soybeans. The residual activity of these herbicides was determined by bioassay, using the same sorghum cultivars evaluated in the field during the period from 0 to 200days after application the treatments. The sorghum crop showed high sensitivity to residual activity of the herbicide sulfentrazone, diclosulam and imazethapyr dose of 0,100 kg ha-1, even when grown after soybean harvest. Furthermore, the residual activity of sulfentrazone exceeded the range of assessment of bioassay, and more than 200 days.